Effect of Rectangular and Triangle Passing Training on U-12 Football Passing Ability - Martin Sudarmono; Sulthon Khaidar Yahya (Universitas Negeri Semarang, 2026)
This research is motivated by the low passing ability of 12-year-old soccer players at the BINA LIGA Pemalang Football School, which can be seen from the lack of accuracy of passes and the frequent loss of the ball during the game. This study aims to determine the effect of rectangular passing and triangle passing exercises on players' passing abilities and compare the effectiveness of the two training methods. The research uses a quantitative approach with experimental methods and pretest-posttest design. The research sample amounted to 20 U-12 players who were divided into two groups using saturated sampling techniques. The research instrument used a short pass test to measure a player's passing ability. The treatment was given for 16 meetings with a frequency of exercise three times a week. Data analysis was carried out using normality, homogeneity, and t-test tests. The results showed that both training methods had a significant influence on improving passing ability with a significance value of 0.000 < 0.05. The average passing value of the quadrilateral group increased from 170.00 to 315.00, while the triangular group increased from 170.00 to 330.00. The conclusion of this study is that the practice of square passing and triangular passing is effective in improving passing ability, but the practice of passing triangle is more effective than the passing of the triangle.